Micromixer‐Assisted Co‐Precipitation Method for Fast Synthesis of Layered Ni‐Rich Materials for Lithium‐Ion Batteries. Issue 12 (20th May 2019) - Liu, Mingyue; Liu, Na; Tan, Jing; Su, Yuefeng; Deng, Wensheng; Chen, Lai; Xue, Ruixue; Zhang, Qiyu
Abstract: Uniform element distribution is a key factor that influences the performance of Ni‐rich cathode materials. Herein, the Ni‐rich LiNi0.8 Co0.1 Mn0.1 O2 cathode material has been synthesized with the assistance of a micromixer, which provides ultrafast and homogeneous mixing environments to endow the products with uniform composition distribution. As‐prepared LiNi0.8 Co0.1 Mn0.1 O2 delivered a high initial discharge capacity of 188.5 mAh g −1 at a 0.2 C rate with a 4.3 V cut‐off potential and reached 95.4 % capacity retention after 50 cycles. LiNi0.6 Co0.2 Mn0.2 O2 and LiNi0.9 Co0.1 O2 synthesized through this method also exhibited reasonable electrochemical performances, which indicates the feasibility of this novel micromixer‐assisted co‐precipitation method in the synthesis of layered cathode materials. Moreover, the reaction time had been reduced from 12 h to only seconds with the assistance of the micromixers when compared to the traditional co‐precipitation method. Abstract : In the mix : Owing to the effective dispersion and homogeneous reaction in a micromixer, the Ni‐rich LiNi x Co y Mn(1 ‐x‐y ) O2 cathode materials prepared with a micromixer exhibit excellent physicochemical and electrochemical properties. The transition metal and alkaline solution in the micromixer collide at a molecular scale. Simultaneously, the uniform element distribution is a key factor, increasing the properties of the products.